2007
DOI: 10.1097/01.sap.0000250648.70177.4a
|View full text |Cite
|
Sign up to set email alerts
|

Reduction Mammaplasty and Sensitivity of the Nipple-Areola Complex

Abstract: W omen requesting reduction mammaplasty are generally more concerned with the improvement of the size and shape of their breasts than with the preservation of mammary sensation. Even after surgery, if not specifically asked, many patients do not mention changes in the sensitivity of the nipple and areola. The improved appearance of the breasts causes a positive change in body image 1-5 and makes the patients feel more sensual, 2,6,7 irrespective of the actual breast sensation. 6 It is therefore not surprising … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…Another consideration is that the middle-aged patient with hypertrophic breasts has indeed experienced additional long-term but subclinical insult to intercostal nerves perhaps due to the increased weight and increased pull by gravity and resultant traction injury to nerves over several decades of life as theorized in previous reports. 6,15 Although the bulk of the literature on reduction mammaplasty has focused on the best techniques to minimize scarring and improve the shape and contour of the breasts, more recent reports have been designed to address more nuanced outcomes including sensation. 9,15,16 Published reports concerning potential alteration of breast sensitivity after reduction mammaplasty have produced conflicting results regarding the area of the breast that was most sensitive and whether breast size influences sensation.…”
Section: Discussionmentioning
confidence: 99%
“…Another consideration is that the middle-aged patient with hypertrophic breasts has indeed experienced additional long-term but subclinical insult to intercostal nerves perhaps due to the increased weight and increased pull by gravity and resultant traction injury to nerves over several decades of life as theorized in previous reports. 6,15 Although the bulk of the literature on reduction mammaplasty has focused on the best techniques to minimize scarring and improve the shape and contour of the breasts, more recent reports have been designed to address more nuanced outcomes including sensation. 9,15,16 Published reports concerning potential alteration of breast sensitivity after reduction mammaplasty have produced conflicting results regarding the area of the breast that was most sensitive and whether breast size influences sensation.…”
Section: Discussionmentioning
confidence: 99%
“…Kuzbari and Schlenz [21] concluded that inferior pedicle techniques are preferable when trying to preserve the areola innervation. In their study, most patients treated with an inferior pedicle kept or improved their original sensitivity after 3 weeks, and 3, 6, and 12 months.…”
Section: Questionnaires Used In the Studymentioning
confidence: 98%
“…The reduced sensitivity did not seem to affect the normalisation of the quality of life, indicating that patients are happy as long as the breast looks good and weighs less Á that is, ''sensuality over sexuality'' [21]. Table II.…”
Section: Questionnaires Used In the Studymentioning
confidence: 98%
See 2 more Smart Citations